Human Brown Fat and Obesity: Methodological Aspects - Van Marken Lichtenbelt, Wouter D. (Frontiers in Endocrinology, 2011)
Much is known about brown adipose tissue in rodents. Its function is to generate heat in response to low environmental temperatures and to diet or overfeeding. The knowledge about BAT in humans is still rather limited despite the recent rediscovery of its functionality in adults. This review highlights the information available on the contribution of BAT in increasing human energy expenditure in relation to obesity. Besides that methodological aspects will be discussed that need special attention in order to unravel the heat producing capacity of human BAT, the recruitment of the tissue and its functionality.